Gender between text and reality An applied study in the novel “Alasud yaliq bik” - Rabab Hussein muneer ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
One of the concepts that have become popular for women's access to their rights and equality with men is gender, and it examines the image of women and men drawn by society according to inherited customs and traditions away from biological features. The issue of gender is the role of men and women imposed on them by society   .    The research is based on tracing this societal vision in the novel "Lions are worthy of you" after presenting the efforts of researchers who studied gender such as :Abdullah Al-Ghadami and Abdullah Ibrahim. And "black benefits you" can be considered a gender text because it shows the relationship of a man and a woman. By extrapolating the text with its linguistic, objective and constructive events and Jokes, it was ensured that the text is in harmony with reality, including male bullying and women's rebellion against reality in order to reach actual equality, not just verbal.